2020
DOI: 10.3390/ijerph18010187
|View full text |Cite
|
Sign up to set email alerts
|

Normative Hand Strength of Healthcare Industry Workers in Central Taiwan

Abstract: Objectives: The purpose of this study is to establish the norms of hand grip strength in the healthcare industry in Taiwan and propose models to predict the strength of hand movement by regression with demographic and anthropometric factors. Methods: This is a cross-sectional study with a stratified convenience sample of workers in healthcare service industries in central Taiwan. Three hundred twenty-nine healthy subjects were recruited. Strength of different hand movement were tested three times in both hands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…The pattern of changes in muscle strength, measured by HGS, was similar to other research findings among other populations, that HGS peak in young adulthood and, after a plateau, start decreasing gradually during ageing 2,14,27 . In line with previous studies, our study revealed a higher HGS value in men than in women 4,11,19,28–30 . Data from some studies showed that muscle mass and strength seem to decline with age.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The pattern of changes in muscle strength, measured by HGS, was similar to other research findings among other populations, that HGS peak in young adulthood and, after a plateau, start decreasing gradually during ageing 2,14,27 . In line with previous studies, our study revealed a higher HGS value in men than in women 4,11,19,28–30 . Data from some studies showed that muscle mass and strength seem to decline with age.…”
Section: Discussionsupporting
confidence: 91%
“…16 The PURE study that assessed grip strength in adults aged 35-70 who reside in 21 countries suggested that individual HGS measurements should be interpreted using region-specific reference ranges. 17 Although some studies have explored the HGS values among Asian people, 11,18,19 they focused on elders or in a selected population, for example, in healthcare industry workers, lacking data with a broad age range in a general unselected population.…”
Section: Introductionmentioning
confidence: 99%
“…Employees who performed work with high physical demands were anticipated to achieve higher HGS scores. This was confirmed in the studies by Lo at al. (2021) and Rostamzadeh et al (2020b) who found HGS of manual workers was significantly stronger than that of non-manual workers or healthcare workers.…”
Section: Theme 3: the Influence Of Biological And Functional Factors ...supporting
confidence: 81%
“…It has been widely acknowledged that age and gender influence HGS with men found to be stronger than women and younger adults stronger than older adults (Agnew and Maas, 1982;Dodds et al, 2016;Günther et al, 2008;Massy-Westropp et al, 2011;Mathiowetz et al, 1985;Wang et al, 2018). Previous studies have also discussed the potential influence other biological and functional factors have on HGS including hand dominance (Bohannon et al, 2006;Günther et al, 2008;Wang et al, 2018), different types of occupation (Günther et al, 2008;Josty et al, 1997;Lo et al, 2021;Rostamzadeh et al, 2019Rostamzadeh et al, , 2020bSaremi and Rostamzadeh, 2019) and anthropometric characteristics (Angst et al, 2010;Eidson et al, 2017;Lo et al, 2021;Massy-Westropp et al, 2011;Mohammadian et al, 2015;Rostamzadeh et al, 2019Rostamzadeh et al, , 2020aSaremi and Rostamzadeh, 2019;Shim et al, 2013;Wang et al, 2018). The correlation between HGS and these additional functional and biological factors is found to be varied.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the pulling strength of Mexicans is significantly different from that of Americans [ 29 ]. Furthermore, compared with the results from international studies, the hand strength of both genders in the manufacturing and healthcare industries in Taiwan was significantly lower (59% to 64%) than that of U.S. and European countries [ 15 , 30 ]. A study conducted by Or et al showed that the pull strength for American participants was 41.2–91.6% greater than that of Chinese participants [ 16 ].…”
Section: Introductionmentioning
confidence: 92%